2013
DOI: 10.1007/978-3-642-35485-4_9
|View full text |Cite
|
Sign up to set email alerts
|

RoboEarth Action Recipe Execution

Abstract: The ability of reusing existing task execution plans is an important step towards autonomous behavior. Today, the reuse of sophisticated services allowing robots to act autonomous is usually limited to identical robot platforms and to very similar application scenarios. The approach presented in this paper proposes a way to mitigate this limitation by storing and reusing task plans on a global accessible database. We describe the task execution engine for the RoboEarth project [26] to demonstrate its ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Based on the above efforts, the author identified that a model for end effectors, sensors, constraints and results must be added to the definition of robot capabilities that was provided in the introductory section to fully represent robot capabilities for manufacturing applications. The author has also identified in the literature an approach that uses an analogous framework to deal with robot capabilities (di Marco et al , 2012). While this other approach targets mobile robots, many components of the framework are akin to the ones described in this paper, thus further demonstrating how crucial these components are for an optimal use of robot capabilities.…”
Section: Robot Capability Componentsmentioning
confidence: 99%
“…Based on the above efforts, the author identified that a model for end effectors, sensors, constraints and results must be added to the definition of robot capabilities that was provided in the introductory section to fully represent robot capabilities for manufacturing applications. The author has also identified in the literature an approach that uses an analogous framework to deal with robot capabilities (di Marco et al , 2012). While this other approach targets mobile robots, many components of the framework are akin to the ones described in this paper, thus further demonstrating how crucial these components are for an optimal use of robot capabilities.…”
Section: Robot Capability Componentsmentioning
confidence: 99%
“…They are very reusable and flexible at adapting to dynamic changes, thus avoiding to have to re-compile the application and its logic whenever a change is needed. Being in the cloud makes ontologies even more reusable, since different robots can exploit them, as was the case with e.g., RoboEarth [15].…”
Section: A Knowledge Managermentioning
confidence: 99%